Releasing Constraints to Growth or Pushing on a String? The Impact of Credit, Training, Business Associations and Taxes on the Performance of Mexican Micro-Firms - Fajnzylber, Pablo (World Bank, Washington, DC, 2012)
The authors employ propensity score matching and a traditional control function approach to examine the impact of participation in various societal institutions on microfirm performance in Mexico. They find that firms that participate in credit markets, receive training, pay taxes, and belong to business associations exhibit significantly higher profits, even after controlling for the various factors that drive participation in those institutions. They also find that firms that borrow from formal or informal sources and those that pay taxes are significantly more likely to stay in business, but firms that received credit exhibit lower rates of income growth. Overall, the results suggest that even if the best performing micro-firms are more likely to be selected into participating in societal institutions, causality also runs in the opposite direction. In particular, increases in strictly or broadly defined formality have the potential for increasing profits and survival rates, and appear to bring micro-firms closer to their optimal sizes.